“Evaluación de cuatro dosis de tri hormona enriquecido con micro nutrientes en el cultivo de cebolla china (var roja chiclayana), en el distrito de Lamas” - Huaraca Ramos, Percy Julian (2015)
This research was conducted in order to determine the dose of hormona tri organic micronutrients (Auxicrop) with better effect for the production of Chinese Onion (Allium fistulosum). This research was developed in the farm "THE PACIFIC" owned by lng. Jorge Luis Pelaez Rivera, located in the Lamas District, Province of Lamas, San Martín Department. Statistical design of randomized complete block (RCBD) with tour blocks, five treatments and a total of 20 experimental units was applied. Data processing was performed with the SPSS 19 program which uses the P-value comparison statistical confidence levels 0.01 and O.OS for the analysis of variance and Duncan test at P <O.OS probability. 250, 500, 750 and 1000 Auxicrop ml.ha-1 Application and without treatment (control) were applied. The most salient findings were that the implementation of 1000 ml.ha-1 (T4) and 750 ml.ha-1 (T3) has reached the highest averages in performance with 87,037.5 kg ha-1 and 63,800.0 kg ha-1; 174.1 g and 127.6 g weight of the plant; 3.31 cm and 2.83 cm diameter bulb respectively. In economic analysis determinad that with an application 750 trihormona ml.ha-1 (T3) the highest value B I C with 0.89 anda net profit of SI was obtained. 14382.65 soles and growing applications doses of tri hormone enriched with micronutrients (Auxicrop) and comparad to treatment TO (control) determinad positiva linear responses of the dependent variables evaluated (neck diameter of the plant, diameter of the bulb, plant length, weight and performance of the plant). Keywords: Micronutrients, green onion, treatments, economic analysis